Changing dimensions in economic development : theories and empirics - Mazumdar, Debashis; Bhattacharyya, Rajib (Emerald Publishing Limited, 2026)
In today's interconnected world, the strategic interaction between the goals of different countries plays a crucial role in achieving meaningful results. Economic development in particular should be analysed as a multi-faceted, nonlinear, and dynamic process, with systematically shifting interaction patterns that require changes in policies and institutions. Changing Dimensions in Economic Development: Theories and Empirics examines the shift from the traditional welfare approach into a non-welfarist approach, which allows for treating individual welfare as multi-dimensional and takes into account the notions of capability, freedom of choice, and social justice. By exploring the different dimensions of interdisciplinary research on development economics and its shifting paradigms, approaches can be devised to develop more comprehensive and effective strategies to promote inclusive and sustainable development globally. As the field continues to evolve, paradigms within development economics will shift to reflect the transformative power of ideas. The dynamic nature of this field demands a willingness to challenge established norms, question assumptions, and embrace innovative approaches which will appeal to academics and practitioners alike.